James Samuel Irwin papers - Irwin, James Samuel, 1820-1894.; Irwin, John Maclay, -1856.
Photocopies of twenty amended typewritten transcriptions of Irwin's letters (1849-1852) from California gold fields, together with photocopies of two of the handwritten originals; will (1854) of Irwin's father, John Maclay Irwin; letter (1878) written by Will Bovard from New Orleans, La., during a yellow fever epidemic; and genealogical notes, obituaries, and photograph.
Lawyer of Pittsfield and Jacksonville, Ill.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bovard, Will -- Correspondence; Irwin family; Gold mines and mining -- California; Lawyers -- Illinois; Yellow fever -- Louisiana -- New Orleans -- 19th century; Lawyers